2016
DOI: 10.20896/saci.v4i1.192
|View full text |Cite
|
Sign up to set email alerts
|

India-Pakistan: Contours of Relationship

Abstract: Even after about 70 years of separation, India and Pakistan continue to live in the prison of the past. The rhetoric of partition is still alive in the memory of the people of both the countries. They have constructed fixed, unchanging and competing images for each other. While Pakistan became an Islamic Republic, India adopted secularism, thereby, negating the two-nation theory. The 'differences' along with memories of partition has made Indian and Pakistani to remain in permanent hostile situation. The leade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
1
0
1
Order By: Relevance
“…In India, the dominant study issues discussed by previous researchers showed no less interesting results than those in previous countries. Dominant research issues in the study room of Islamic political parties in India are mostly related to Islamic political parties in other countries that are still neighbors of India, such as Pakistan (Chengappa, 2001;Mittal & Ranjan, 2016;Nazar, 2016), Bangladesh (Datta, 2003(Datta, , 2007Mitter, 2016), and Syria (Rath, 2017). The geographical location of neighboring countries and the long history of conflict between Islamic groups in India underlies researchers in India to carry out this research.…”
Section: Dominant Issues In the Study Of Islamic Political Partiesmentioning
confidence: 99%
“…In India, the dominant study issues discussed by previous researchers showed no less interesting results than those in previous countries. Dominant research issues in the study room of Islamic political parties in India are mostly related to Islamic political parties in other countries that are still neighbors of India, such as Pakistan (Chengappa, 2001;Mittal & Ranjan, 2016;Nazar, 2016), Bangladesh (Datta, 2003(Datta, , 2007Mitter, 2016), and Syria (Rath, 2017). The geographical location of neighboring countries and the long history of conflict between Islamic groups in India underlies researchers in India to carry out this research.…”
Section: Dominant Issues In the Study Of Islamic Political Partiesmentioning
confidence: 99%
“…Akibat konflik komunal berbasis SARA menjadikan negara ini terpecahbelah dan menelan korban dalam jumlah yang sangat banyak. India terpecah menjadi dua yaitu Pakistan dan India (Mittal & Ranjan, 2016). Sementara konflik berbasis komunal di Yugoslavia yang terdiri dari berbagai suku mengakibatkan genosida etnis besar-besaran dan disebut sebagai konflik genosida terbesar setelah perang dunia kedua.…”
Section: Tren Konflik DI Indonesiaunclassified